Urocortin and cardiovascular protection - HUANG Yu; YAO Xiao-qiang; LAU Chi-wai; CHAN Yau-chi; TSANG Suk-ying; CHAN Franky Leung (Acta Pharmacologica Sinica, 2016)
Urocortin and other hypothalamus corticotropin-releasing factor (CRF) polypeptides play biologically diverse roles in the stress, cardiovascular and inflammatory responses by acting on central and peripheral CRF receptors. Urocortin shows a significantly high sequence homology to CRF, and the concurrent expression of type-2 CRF (CRF2) receptors with urocortin in the heart suggests that urocortin may play a physiological role in the cardiac function. Urocortin is thought to be the endogenous agonist producing the cardiovascular actions previously attributed to CRF. This review highlights the current novel findings on the molecular and cellular mechanisms by which urocortin may exert its cardiovascular protective action.